English Section - Chasqui, Revista (Chasqui. Revista Latinoamericana de Comunicación, 1983)
Editorial Dr. Luis Eladio Proaño; Chasqui interview a Fausto Izcaray; Education in an informatics society Héctor Schmucler; Communication Satellites: a third world perspective Neville Jayaweera; Controversy de Sola Pool/Schiller; The microelectronics revolution: implications for the third world Juan R. Rada; Broadcasting in Asia: a sleeping Giant? Sarath Amunugama